2007
DOI: 10.1021/ic700915z
|View full text |Cite
|
Sign up to set email alerts
|

Fast Synthesis of ZnO Nanostructures by Laser-Induced Decomposition of Zinc Acetylacetonate

Abstract: A CO2 laser (lambda = 10.6 microm) was used to heat a solution of water and alcohol saturated by Zn(AcAc)2 on a fused quartz substrate in open air. After only a few seconds of irradiation, various zinc oxide (ZnO) nanostructures including nanorods and nanowires are formed near the center of the irradiated zone, surrounded by a porous thin film of ZnO nanoparticles. The type of structures produced and their localization on the substrate can be varied by selecting adequate irradiation time and laser power ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Fauteux et al recently demonstrated that laser-induced decomposition of the Zn(AcAc) 2 resulted in the ZnO nanostructures formation [19]. It has successfully being used in MOCVD growth process to grow aligned hexagonal nanorods and whiskers, nanotube arrays and thin films at temperature range 500 -650 °C on various substrates [20].…”
Section: Precursors Chemistrymentioning
confidence: 99%
“…Fauteux et al recently demonstrated that laser-induced decomposition of the Zn(AcAc) 2 resulted in the ZnO nanostructures formation [19]. It has successfully being used in MOCVD growth process to grow aligned hexagonal nanorods and whiskers, nanotube arrays and thin films at temperature range 500 -650 °C on various substrates [20].…”
Section: Precursors Chemistrymentioning
confidence: 99%
“…Some of the methods for the preparation of ZnO from zinc acetylacetonate include CO 2 laser decomposition [15], chemical spray deposition [16] or solution chemistry methods in alcoholic solutions with the presence of a surfactant [17] or an inorganic base [18].…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned methods have the disadvantage of long processing time or low growth rates limiting the possibility of a scale-up. In order to overcome this disadvantage, many groups have developed methods that are simple but fast, such as inductive heating [19], microwave heating [20], resistive heating [21], and laser induced decomposition [22]. A typical growth rate of 16 nm/s was obtained for ZnO nanowires synthesized through inductive heating [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual growth rate of ZnO nanowires was not reported [21]. The deposition rate of 880 nm/s, demonstrated by Fauteux et al [22] for ZnO nanowires grown through laser induced decomposition of zinc acetylacetonate using a CO 2 laser, although the best till date, is limited by reproducibility issues.…”
Section: Introductionmentioning
confidence: 99%